2013
DOI: 10.1007/s10802-012-9704-x
|View full text |Cite
|
Sign up to set email alerts
|

Time Doesn’t Change Everything: The Longitudinal Course of Distress Tolerance and its Relationship with Externalizing and Internalizing Symptoms During Early Adolescence

Abstract: Although distress tolerance is an emerging construct of empirical interest, we know little about its temporal change, developmental trajectory, and prospective relationships with maladaptive behaviors. The current study examined the developmental trajectory (mean- and individual-level change, and rank-order stability) of distress tolerance in an adolescent sample of boys and girls (N=277) followed over a four-year period. Next we examined if distress tolerance influenced change in Externalizing (EXT) and Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
85
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 86 publications
12
85
1
1
Order By: Relevance
“…In contrast, ODD was not related to frustration tolerance (i.e., quit status) in our sample. It should be noted that the distress tolerance task used by Cummings et al (2013) was different from the one used in this study, which may have contributed to differential results. In addition, study design (i.e., Cummings et al being a longitudinal study vs. this cross-sectional study) may have contributed to different findings.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, ODD was not related to frustration tolerance (i.e., quit status) in our sample. It should be noted that the distress tolerance task used by Cummings et al (2013) was different from the one used in this study, which may have contributed to differential results. In addition, study design (i.e., Cummings et al being a longitudinal study vs. this cross-sectional study) may have contributed to different findings.…”
Section: Discussionmentioning
confidence: 90%
“…Specifically, due to this methodological approach, we cannot rule out that both changes in DI and symptoms were attributable to maturation or regression to the mean. However, unlike symptoms of mood and anxiety disorders that may improve over time without intervention, DI is hypothesized to be a stable, trait-like variable requiring targeted treatment to modify (Cummings et al, 2013; Leyro et al, 2010), which mitigates this concern to some degree. Given that assessments were conducted at pre- and post-treatment, it is not possible to definitively establish temporal precedence of changes in DI and other symptoms (e.g., whether changes in DI preceded changes in other symptoms).…”
Section: Discussionmentioning
confidence: 99%
“…Although much of the research on DI has focused on substance use disorders, recent research has highlighted the relevance of this risk factor in depression and anxiety (e.g., Cummings et al, 2013; Daughters et al, 2009). DI is associated with greater severity of symptoms of internalizing disorders, such as posttraumatic stress disorder (Marshall-Berenz et al, 2010; Vujanovic, Bonn-Miller, Potter, Marshall, & Zvolensky, 2011), social phobia (Macatee & Cougle, 2013), panic disorder (Marshall et al, 2008; Schmidt et al, 2006), and depression (Magidson et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This study used data from a larger, longitudinal study of behavioral, environmental, and genetic mechanisms of HIV-related risk behaviors in youth. Details of the larger longitudinal study have been reported elsewhere (e.g., Cummings et al, 2013;MacPherson et al, 2010). In brief, participants were a sample of youth and their parents recruited in the greater metropolitan Washington, D.C., area via media outreach and mailings to area schools, libraries, and Boys and Girls Clubs.…”
Section: Participantsmentioning
confidence: 99%